Sosialisasi Dampak dan Manfaat Tanaman Mangrove Bagi Ekosistem Lingkungan di Teluk Pangpang - Hadi Prayitno; Daniel Dewantoro Rumani; Ariyono Setiawan; Untung LN Wibowo; Ahmad Mubarok; Dede Ardian; Ikhwanul Qiram (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
A mangrove forest ecosystem is a forest that grows and develops in a coastal area, that is, in a marshy land area in a brackish water area. Kedunghasri is the easternmost village, where waste is channeled from upstream to downstream due to lack of discipline on waste management within the community. Through this charity, 500 mangrove trees can be planted to prevent pollution of marine ecosystems. The results of the activities show that planting mangrove trees can raise awareness that mangrove trees are very influential.